Optimal Peak Regulation Strategy of Virtual and Thermal Power Plants - Li, Peng; Chen, Yuanfeng; Yang, Kang; Yang, Ping; Yu, Jingyi; Yao, Senjing; Zhao, Zhuoli; Lai, Chun Sing; Zobaa, Ahmed F.; Lai, Loi Lei (Frontiers in Energy Research, 2022)
To achieve the national carbon-peak and carbon-neutral strategic development goals, it is necessary to build power systems dominated by renewable and sustainable energy. The future power system with a high proportion of renewable and sustainable energy is required to have large-scale, low-cost, flexible and adjustable resources. To this end, this paper aggregates user-side distributed energy storage and electric vehicles into a virtual power plant, considering the uncertainty of wind power fluctuations and the uncertainty of electric vehicle charging and discharging to establish a day-ahead and intra-day peak regulation model for combined peak regulation of virtual and thermal power plants. The bounding algorithm seeks the optimal strategy for the two-stage model of joint peak regulation, and obtains the day-ahead and intra-day two-stage optimal peak regulation strategy. The simulation example shows that the virtual power plant and its day-ahead and intra-day optimal peak regulation strategy can reduce the peak regulation cost of the power system, as compared with the deep peak regulation of thermal power plants with a special supporting energy storage power station. This work provides a global perspective for virtual power plants to participate in the formulation of power system peak regulation rules.